Adaptive management for the sustainable exploitation of lagoon resources in remote islands: lessons from a massive El Niño-induced giant clam bleaching event in the Tuamotu atolls (French Polynesia). (10th April 2017) - ANDRÉFOUËT, SERGE; VAN WYNSBERGE, SIMON; KABBADJ, LINA; WABNITZ, COLETTE C.C.; MENKES, CHRISTOPHE; TAMATA, THIERRY; PAHUATINI, MICHEL; TETAIREKIE, IOTEFA; TEAKA, IOSUA; SCHA, TEIKI AH; TEAKA, TAIHOPU; REMOISSENET, GEORGES
SUMMARY: Small-scale mariculture of high-value species for trade in remote islands can offer valuable alternative livelihoods to local communities. The endangered giant clam species Tridacna maxima is naturally abundant in some atolls in French Polynesia (FP) and has been the focus of commercial mariculture activities since 2012. Shortly after spat collectors became operational in two atoll lagoons, FP rose to become one of the main exporters of giant clams for the aquarium trade. However, this activity has been threatened recently by a mass clam-bleaching event triggered by the 2015–2016 El Niño. This study reviews the roles that international (Convention on International Trade in Endangered Species of Wild Fauna and Flora) and national regulatory frameworks play in the development of this activity in a small island context, and how they can indirectly promote better science and monitoring in order to inform adaptive management strategies. The links between the nine main groups of stakeholders show the necessary adaptation measures required to mitigate climate-driven mortalities. While this case study remains specific to giant clam farming in FP, general lessons are provided that could help in mitigating economic impacts from climate-related events on other islands.